Positive effects of online games on the growth of college students: A qualitative study from China - Li, Feiyue; Zhang, Di; Wu, Suowei; Zhou, Rui; Dong, Chaoqun; Zhang, Jingjing (Frontiers in Psychology, 2023)
Objectives: This study aimed to explore the positive effects of online games on college students’ psychological demands and individual growth. Methods: A descriptive qualitative study design was carried out from September to December 2021. Semistructured, in-depth, and individual interviews were conducted with a purposive sample of 20 undergraduates who played the online game ‘Glory of Kings’ from 6 universities. Thematic analysis was employed to explore the positive features caused by ‘Glory of Kings’. Results: College students reported three positive effects of online games, namely, satisfying the need for personal growth, meeting the requirement of social life and promoting academic performance. Conclusion: College educators and families should take advantage of the positive effect of online games to guide college students to use online games reasonably.